Acilenaminonas: síntese e aplicação na obtenção de pirazóis, pirazolo[3,4-d]piridazinonas e pirazolo[1,5-a]pirimidinas - Rosa, Fernanda Andreia (2009)
The regioespecific synthesis of a series of 14 N-acylated enaminones (52-88%) from the acylation reaction of secondary β-enamino ketones [RC(O)CH=CHNR1R2; R = Ph, 4- FC6H4, 4-NO2C6H4, thien-2-yl, CCl3, CF3; R1 = H; R2 = Bn, Ph, 4-NO2C6H4] with trifluoroacetic anhydride or ethyl oxalyl chloride in pyridine is reported. On the other hand, when tertiary enaminone precursors [R = Ph, 4-MeC6H4, 4-MeOC6H4, 4-BrC6H4, 4-ClC6H4, 4-FC6H4, 4-O2NC6H4, thien-2-yl, benzofur-2-yl, CCl3, CF3; R1,R2 = Me] were used, the acylation reaction led to a series of 17 C-acylated enaminones (75-95%). A series of 4-substituted-1H-pyrazole-5-carboxylates (73-94%) were obtained regiospecifically from the cyclocondensation reaction of non symmetrical enaminodiketones [RC(O)C(=CHNMe2)C(O)CO2Et; R = Ph, 4-MeOC6H4, 4-ClC6H4, 4-FC6H4, 4-O2NC6H4, thien-2-yl, benzofur-2-yl, CCl3, CF3] with tert-butylhydrazine or carboxymethylhydrazine. The reaction of these pyrazole-5-carboxylates (R = 4-MeOC6H4, 4-FC6H4, benzofur-2-yl, CF3) with hydrazine lead to synthesis of 4- substituted-pyrazolo[3,4-d]pyridazinones (74-96%). In addition, the reaction of enaminodiketones (R = Ph, 4-MeC6H4, 4-MeOC6H4, 4-BrC6H4, 4-ClC6H4, 4-FC6H4, 4- O2NC6H4, thien-2-yl, benzofur-2-yl) with 3-amino-5-methylpyrazole was performed, where a series of pyrazolo[1,5-a]pyrimidine-7-carboxylates were obtained regiospecifically (53-79%).